Comparative Analysis of Effective Lens Position and Refractive Outcomes in Scleral-Fixated versus Intracapsular Intraocular Lenses - Trivedi V; Lee S; Lee PSY; Me R; You Q; Im J; Ross B; Tran DV; Le KH; Malbin B; Lin X (Clinical Ophthalmology)
Vichar Trivedi,1 Stacey Lee,1 Patrick SY Lee,1 Rao Me,1 Qisheng You,1 Jacob Im,1 Bing Ross,1 David V Tran,1 Kim Hoang Le,2 Brett Malbin,1 Xihui Lin1 1Department of Ophthalmology, Visual and Anatomical Sciences, Kresge Eye Institute/Wayne State University School of Medicine, Detroit, MI, USA; 2Department of Ophthalmology, Henry Ford Hospital, Detroit, MI, USACorrespondence: Xihui Lin, Kresge Eye Institute, Department of Ophthalmology, Visual and Anatomical Sciences, Wayne State University School of Medicine, 4717 St. Antoine Street Detroit, Detroit, MI, 48201, USA, Tel +1 313 577-8900, Email xihui.lin@wayne.eduPurpose: To evaluate the outcomes of scleral-fixated intraocular lenses (IOLs) implanted using either Yamane technique or Gore-Tex suture fixation, in comparison to intracapsular lens fixation, and to assess the efficacy of various lens formulas in achieving predicted refractive targets.Patients and Methods: This study included 45 eyes from 44 patients with scleral-fixated IOLs, comprising 37 Yamane eyes and 8 Gore-Tex eyes. Preoperative refractive predictions from various formulae were compared with final postoperative refraction. Outcomes assessed included effective lens position (ELP), postoperative predictive error, and changes in visual acuity. The ELP of scleral-fixated IOLs was compared with that of intracapsular IOLs in fellow eyes.Results: Average ELP for Yamane IOLs was 0.62 mm more posterior relative to intracapsular IOLs but was not significantly different for Gore-Tex IOLs. Average postoperative logMAR acuity change was significant at – 1.30 (p=4.5x10− 11) and – 1.65 (p=5x10− 4) for Yamane and Gore-Tex eyes, respectively. Mean prediction error for Yamane eyes was +0.29± 1.3 D, − 0.53± 0.40 D, +0.80± 1.4 D, and +0.43± 1.4 D using Barrett Universal II, Holladay, Hill-RBF, and Hoffer QST formulas, respectively. Mean prediction error for Gore-Tex eyes was – 0.37± 1.24 D and +0.53± 1.19 D using Barrett Universal II and Holladay formulas, respectively.Conclusion: Different scleral fixation techniques result in variations in ELP compared to intracapsular IOL placement. In our hands, when using the Yamane technique, surgeons should aim for a myopic refractive target to offset hyperopic errors when employing the Barrett Universal II, Hill-RBF, or Hoffer QST formulas, and a hyperopic target when using the Holladay formula. For Gore-Tex IOLs, a slightly hyperopic target is recommended to counter myopic error when using the Barrett Universal II formula, whereas a slightly myopic target is advised with the Holladay formula to offset hyperopic error. A limitation of our study is the small sample size for patients who underwent Gore-Tex suture fixation.Keywords: secondary intraocular lens, Yamane technique, flanged technique